2023
DOI: 10.1021/acsaom.3c00188
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Photochromic Properties of WO3-Based Materials toward High-Performance Light-Responsive Textiles

Abstract: The development of photoresponsive textiles with high color contrast, sunlight response, fast coloration/bleaching, and reversible properties has been a major quest for anticounterfeiting, camouflage, UV protection, and fashion. WO 3 materials are promising building blocks for textile applications, but their application has been limited by their slow color bleaching under ambient conditions and limited sunlight response. Herein, innovative tungsten oxide-based materials with tunable photochromism were produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
(150 reference statements)
0
6
0
Order By: Relevance
“…The exact process responsible for the photochromic behavior in WO 3 -based materials and composites remains a topic of ongoing discussion and research. However, there is acknowledgment of the significance of defects within the material structure, the presence of an amorphous structure, particle size, and the influence of adsorbed water in this context . The photochromic mechanism has been elucidated in the preceding equations (eqs –).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The exact process responsible for the photochromic behavior in WO 3 -based materials and composites remains a topic of ongoing discussion and research. However, there is acknowledgment of the significance of defects within the material structure, the presence of an amorphous structure, particle size, and the influence of adsorbed water in this context . The photochromic mechanism has been elucidated in the preceding equations (eqs –).…”
Section: Resultsmentioning
confidence: 99%
“…When subjected to simulated solar illumination, electrons within the valence bands of WO 3 and MoO 3 absorb energy, leading to the creation of electron–hole pairs. These electrons are subsequently captured by WO 3 and MoO 3 , forming W 5+ and Mo 5+ , while H + ions from the surrounding air or the sample’s surface are incorporated into WO 3 and MoO 3 , , resulting in the generation of H x WO 3 and H x MoO 3 , accompanied by the reduction of W 5+ and Mo 5+ . The blue coloration of the sample stems from the electron’s transition within the valence band. , WO 3 false( MoO 3 false) + hv WO 3 * false( MoO 3 * false) + normalh + + normale .25ex2ex normalW 6 + false( Mo 6 + false) + normale normalW 5 + false( Mo 5 + false) .25ex2ex normalH 2 O + normalh + normalH + + normalO 2 .25ex2ex WO 3 false( MoO 3 false) + x e + x h + normalH x…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some transition metal oxides show an interesting photochromic effect and can be deeply colored by exposing the material to irradiation with appropriate energy. , Such photochromic phenomena of transition metal oxides have attracted considerable attention because they can be applied to display devices, erasable optical memory media, chemical sensors, smart-windows, and other cutting-edge applications. , Among them, tungsten­(VI) oxide (WO 3 ), a wide-bandgap n -type semiconductor, is mainly the most studied among inorganic photochromic materials because it has characteristics such as chemical stability, coloring efficiency, and fast coloring response time . Many researchers have reported that the hybridization between WO 3 nanomaterials and organic constituents enhances photochromic performance and consider that the monolayer of organic molecules surrounding WO 3 nanomaterials can behave as an active form of organized organic matter. This unique enhanced photochromic phenomenon by organic molecules adsorbed on the metal oxide surface is called “surface-enhanced photochromic phenomenon” . Recently, we have focused on the surface-enhanced photochromic phenomena of colloidal WO 3 in aqueous media in the presence of amino acid compounds and experimentally demonstrated the usefulness of WO 3 nanoparticles as a colorimetric probe for high-sensitive “label-free” detection of amino acid compounds …”
Section: Introductionmentioning
confidence: 99%